2021
DOI: 10.4049/jimmunol.2001022
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Exercise Inhibits Age-Related Inflammation, Liver Steatosis, Senescence, and Tumorigenesis

Abstract: Age-related chronic inflammation promotes cellular senescence, chronic disease, cancer, and reduced lifespan. In this study, we wanted to explore the effects of a moderate exercise regimen on inflammatory liver disease and tumorigenesis. We used an established model of spontaneous inflammaging, steatosis, and cancer (nfkb1 2/2 mouse) to demonstrate whether 3 mo of moderate aerobic exercise was sufficient to suppress liver disease and cancer development. Interventional exercise when applied at a relatively late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Consistent with our results, numerous studies have demonstrated that endurance training exhibits a protective effect against tumourigenesis 19,29,30 . Three months of moderate endurance exercise reduced inflammation and oxidative damage in Nfkb1 −/− mice, thereby reversing hepatic steatosis and preventing tumourigenesis 31 . Epidemiological investigation has also shown that middle‐distance runners and long‐distance runners have the lowest cancer incidence among athletes 32 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, numerous studies have demonstrated that endurance training exhibits a protective effect against tumourigenesis 19,29,30 . Three months of moderate endurance exercise reduced inflammation and oxidative damage in Nfkb1 −/− mice, thereby reversing hepatic steatosis and preventing tumourigenesis 31 . Epidemiological investigation has also shown that middle‐distance runners and long‐distance runners have the lowest cancer incidence among athletes 32 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar results to ours have been reported in other studies (Smart et al, 2018 ; Ye et al, 2019 ). This could be considered the ability of long-term exercise to improve the inflammatory state of the liver by increasing SIRT activity and enhancing the deacetylation of key transcription factors of inflammation and metabolism, such as NF-κB and PGC-1α (Bianchi et al, 2021 ), which in turn improves the state of the liver. Thus, the changes may have benefited from the improvement in inflammatory state of liver.…”
Section: Discussionmentioning
confidence: 99%
“…Several pieces of evidence support a role for tDDR as a driver of ageing and age-associated diseases. First, interventions known to increase health span such as dietary restriction 41 , exercise 42 , rapamycin 43,44 and 17β-oestradiol 45 can reduce the frequency of cells with TAFs. Clearance of senescent cells with senolytic strategies reduces TAF numbers in vivo 36,37,41,46 .…”
Section: Telomere Dysfunction In Ageing and Age-related Diseasesmentioning
confidence: 99%